2021
DOI: 10.1007/s11367-020-01852-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of environmental performance in life cycle assessments—implications for environmental benchmarking

Abstract: Purpose Life cycle assessment (LCA) is considered a robust method to analyse the environmental impacts of products and is used in public and private market applications such as Green Public Procurement (GPP) and Environmental Management Systems (EMS). Despite the usefulness of the methodology, difficulties exist with the interpretation of LCA results. The use of benchmarks can facilitate this process, but there is yet little research on the definition of environmental benchmarks. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Ding and Liu [59] compared three benchmarking approaches, and they propose that policymakers should apply multiple benchmarking tools. Welling and Ryding [60] identified life cycle assessment as an effective method for environmental impact measurement and Hollberg et al [61] found that life cycle assessment-based benchmarks have been used as certification systems on the building level.…”
Section: State Of Researchmentioning
confidence: 99%
“…Ding and Liu [59] compared three benchmarking approaches, and they propose that policymakers should apply multiple benchmarking tools. Welling and Ryding [60] identified life cycle assessment as an effective method for environmental impact measurement and Hollberg et al [61] found that life cycle assessment-based benchmarks have been used as certification systems on the building level.…”
Section: State Of Researchmentioning
confidence: 99%
“…In connection with the problems described above, attempts have been made to develop a new environmental scoring methodology for construction products based on LCA [48]. Benchmarking methods are also used regarding their applicability to the EPD's interpretation [49,50].…”
Section: Sustainability and Construction Productsmentioning
confidence: 99%
“…The included life cycle modules from the EPD. These boundaries are defined according to the standards, concerning the production stage (A1-A3), the construction stage (A4-A5), the use stage (B1-B7), the end-of-life (EoL) stage (C1-C4), and last the benefits beyond the system boundary (D) [12], [13], [18].…”
Section: System Boundariesmentioning
confidence: 99%